Determination of Meat Content in Processed Meats Using Currently Available Methods - Babji, Abdul Salam; Ooi, P. H.; Abdullah, Aminah (1989)
Four methods were used in the determination of meat content in local meat and meat products. Current methods available are not reliable and applicable to routine monitoring and quality control by the regulating laboratories as well as the meat processing industry. A reliable and practical method is needed to monitor meat Introductions and ensure that they are meeting the minimum requirement of sixty five (65 %) percent meat content. The total pigments and hemoglobin technique was found to be applicable for determination of meat content in locally Inocessed beef burgers, when compared to the Modified Method of Stubbs & More (1919), and Pearson Method (1975)